Asteroid trace fossils from Lower Cretaceous shallow- to marginal-marine deposits in Patagonia. (January 2019) - Fernández, Diana E.; Comerio, Marcos; Giachetti, Luciana M.; Pazos, Pablo J.; Wetzel, Andreas
Abstract: Most stellate trace fossils of the ichnogenus Asteriacites are attributed to asterozoan producers in general and the majority is the result of the work of ophiuroids. The fossil record of asterozoans is scarce in South America, particularly for the Mesozoic. Asteriacites specimens found in shallow- to marginal-marine Lower Cretaceous (upper Hauterivian-lower Barremian) deposits in the Neuquén Basin (Patagonia, Argentina) exhibit sculpture and morphometry typical of asteroid producers. This is the second record of asteroids from the Lower Cretaceous of South America. The close association between these Asteriacites possibly produced by astropectinids and traces assignable to Siphonichnidae are suggestive of a predator-prey interaction, adding palaeoecological information for community-structure reconstruction of these deposits. For ichnotaxonomic evaluation, morphometric parameters of Asteriacites were elaborated using simple photogrammetric procedures applied on negative epirelief specimens and undertraces to define edges of the stellate trace fossils. Graphical abstract: Highlights: Second record of asteroids from the Lower Cretaceous of South America. Rare example of asteroid predator-bivalve prey interaction in the fossil record. Photogrammetric procedures used for enhancement of features. Asteriacites attributed to astropectinids and discussion of ichnotaxonomic problems. New paleoecological and paleoenvironmental information for the Asteriacite s-bearing unit.